DESEMPENHO AGRONÔMICO DE LINHAGENS AVANÇADAS DE AMENDOIM NA REGIÃO CONE-SUL DE MATO GROSSO DO SUL - GAIOLA, Lucas Henrique de Oliveira,; SCHWARTZ, Phillip Silva,; GOTTARDI, Gabriel Alves,; OLIVEIRA, João Paulo Zaluchi Souza de,; PESTANA, Carlos Eduardo Skittberg,; ZOZ, Tiago, (ANAIS DO ENIC, 2025)
-